KELAINAN HEMATOLOGI PADA DEMAM BERDARAH DENGUE 1Ni Made Renny A Rena, 2Susila Utama, 2Tuty Parwati M 1 Divisi Hematologi Onkologi Medik, 2 Divisi Penyakit Tropik dan Infeksi Bagian / SMF Ilmu Penyakit Dalam, FK Unud RSUP Sanglah Denpasar Email: renny_ang@ - Renny A Rena, Ni Made; Utama, Susila; Parwati M, Tuty (journal of internal medicine; Vol. 10, No. 3 September 2009, 2012)
Dengue infection can cause a unique and complex alteration to the homeostasis mechanism of the body. The underlying of bleeding, as a more frequent clinical manifestation of dengue was based on multiple factors such as thrombocytopenia, thrombopathy, Disseminated Intravascular Coagulation (DIC), prolonged of bleeding time and prothrombin time, decrease of some coagulation factors, hypoÞ brinogenemia and also increasing of Þ brin degradation products. Beside, kinin and bradikinin sytem was also activated. Endothelial dysfunction as one of coagulopathy disorder in dengue infection patients can shown as some clinical manifestation. Antigen antibody complex of dengue, activated the coagulation system, start from Haegeman factor (factor XII become factor XIIa). Therefore, factor XIIa activated the others coagulation factors respectively until Þ brin are produced, Þ brinolysis system are also activated, plasminogen change become plasmin through enzymatic process. Disseminated intravascular coagulation, is an emergency complication of dengue infection, which occur because activation of coagulation system and decreasing of thrombocyte level. Others condition such as shock, hypoxia, and acidosis also thought to be the factors that cause the DIC. Deterioration of all of the hemopoesis system, which are hypoplasia occur on the beginning of the infection and increasing of erythropoesis after Þ fth day of infection. This is caused by direct suppression of the viral and activation of the proinß ammatory cytokines
Keywords: hematology disorders, dengue infection P